Assessment of platelet-to-lymphocyte ratio in patients with retinal vein occlusion - Bengi Ece Kurtul; Ayșe İdil Çakmak; Ahmet Elbeyli; Deniz Özarslan Özcan; Sait Coșkun Özcan; Veysel Cankurtaran (Therapeutic Advances in Ophthalmology, 2020)
Purpose: To investigate platelet-to-lymphocyte ratio (PLR) in retinal vein occlusion (RVO) patients. Methods: In this study, we retrospectively reviewed data of 32 patients with RVO (RVO group) and 32 age- and sex-matched participants without RVO (control group) between January 2017 and March 2019. The PLR was determined by dividing the platelet count by the lymphocyte count. Results: Age and gender were comparable between the groups ( p  = 0.204 and p  = 0.800, respectively). PLR was significantly elevated in the RVO group compared with the control group (137 (113–164) vs 101 (86–129), p  = 0.001)). In the receiver operator characteristics curve analysis, the optimal cut-off value of PLR for predicting RVO was 123, with 69% sensitivity and 72% specificity. Conclusion: We report that PLR are elevated in RVO, suggesting that PLR may be a useful marker for RVO.